2022
DOI: 10.1186/s13046-022-02266-9
|View full text |Cite
|
Sign up to set email alerts
|

HDAC7 promotes NSCLC proliferation and metastasis via stabilization by deubiquitinase USP10 and activation of β-catenin-FGF18 pathway

Abstract: Background Histone deacetylases (HDACs) play crucial roles in cancers, but the role and mechanism of HDAC7 in NSCLC have not been fully understood. Methods A total of 319 patients with non-small cell lung cancer (NSCLC) who underwent surgery were enrolled in this study. Immunohistochemistry and Kaplan–Meier survival analysis were performed to investigate the relationship between HDAC7, fibroblast growth factor 18 (FGF18) expression, and clinicopath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 48 publications
2
26
0
Order By: Relevance
“…In terms of mechanism, HDAC7 could interact with β -catenin and enhance its nucleus translocation via decreasing β -catenin acetylation level at Lys49 and phosphorylation level at Ser45 to promote fibroblast growth factor 18 expression which induced the malignant biological behaviors of NSCLC, and the HDAC7 expression could be further stabilized by USP10. The similar mechanism could also be found in the study of HDAC6 [ 30 , 31 ]. Besides, several articles have indicated the roles of USP10 in pancreatic cancer.…”
Section: Discussionsupporting
confidence: 75%
“…In terms of mechanism, HDAC7 could interact with β -catenin and enhance its nucleus translocation via decreasing β -catenin acetylation level at Lys49 and phosphorylation level at Ser45 to promote fibroblast growth factor 18 expression which induced the malignant biological behaviors of NSCLC, and the HDAC7 expression could be further stabilized by USP10. The similar mechanism could also be found in the study of HDAC6 [ 30 , 31 ]. Besides, several articles have indicated the roles of USP10 in pancreatic cancer.…”
Section: Discussionsupporting
confidence: 75%
“…In our study, HDAC7 knockdown reversed WNT5A overexpression induced changes in the levels of EMT markers by decreasing SNAIL levels. Furthermore, our research group recently found that HDAC7 increased SNAIL protein levels by regulating fibroblast growth factor 18 (FGF18) in non-small cell lung cancer [ 52 ]. As mentioned above, we speculate that SNAIL regulates E-cadherin expression by recruiting HDAC7 to form a corepressor complex, HDAC7 deacetylates lysine residue sites on the SNAIL protein to affect its stability and regulate the expression of E-cadherin, or HDAC7 indirectly promotes SNAIL by regulating other factors, but these hypotheses require further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, USP10 might affect cisplatin resistance by deubiquitinating and thereby stabilizing the oncogenic protein histone deacetylase 6 (HDAC6) ( 36 , 37 ). Another study showed that USP10 plays an important regulatory role in NSCLC via deubiquitinating and stabilizing histone deacetylase 7 (HDAC7), and that USP10 inhibition could significantly accelerate HDAC7 degradation and impair NSCLC proliferation and migration ( 38 ).…”
Section: Usp Role In Cancermentioning
confidence: 99%